Proposed Financial Strategy of Paid Up Capital Requirement for Bank Sumsel Babel Syariah's Spin Off in 2020 - Faradhipta, Adrian Chandra; Aliludin, Arson (The Indonesian Journal of Business Administration, 2014)
Abstract. Indonesia Banking Act No. 21 issued on 16 July 2008, and Bank Indonesia Regulation No. 11/10/PBI/2009 or known as PBI No.11 regarding Sharia Business Unit enacted on 19 March 2009. Both regulations require all conventional banks which owned Sharia Business Unit (UUS) to spin off their UUS becoming general Islamic Bank or known as Bank Umum Syariah (BUS). Bank Sumsel Babel that has Sharia Business Unit called Bank Sumsel Babel Syariah is also no exception in these regulations. They have to obey the rules and doing spin off at least in 2023.In 2011 Bank Sumsel Babel had already gave a proposal to Bank Indonesia. They already arranged the the scenario of paid up capital. In meantime there are a lot of factors affected Bank Sumsel Babel operation. They just only could gather 232 Billion up till 2014, this lead Bank Sumsel Babel Syariah being struggle with their own plan to do spin off in 2020. In order to find out the solution, the writer of this thesis analyse the available options for Bank Sumsel Babel to get additional paid up capital from various sources. Based on the analyses and some considerations the best option for Bank Sumsel Babel is doing IPO about 25% of it shares to public with totalKeywords: international expansion, market growth strategy, lubricant market, passenger cars and pickup trucks sectors, flanking strategy, Hambrick and Fredrickson’s framework of strategy.